Identification of Adaptive Capacity Assessments to Improve Collective Adaptation of Farmers to Climate Change - Wulansari, Ica; Abdoellah, Oekan S; Gunawan, Budhi; Parikesit (Asian Journal of Agriculture and Rural Development, 2021)
Collective adaptation is a relevant discussion in association with the limited adaptive capacity of farmers to deal with climate change. This study aims to improve the collective adaptation of farmers through the identification of adaptive capacity assessments. A collective adaptation mechanism in the form of planning for rice planting time has succeeded in reducing the vulnerability of farmers. This study was conducted at a rice production center with a collective adaptation mechanism in Indramayu District, West Java Province, Indonesia. The data were collected using a quantitative method through a questionnaire distributed to 296 farmer respondents and a qualitative method through structured interviews. The observations provided an overview for authors to build structured interviews. The results of the study show that the adaptive capacity of farmers is supported by social capital and collective adaptation mechanisms of farmers consisting of trust in the formal leaders, quality of collective decisions, and planning capacity. The results of this study contribute to the implementation of public policies in order to support the successful implementation of adaptation strategies to deal with climate change in accordance with the needs of farmers.